Guinea : Third Review Under the Extended Credit Facility Arrangement, Request for Modification of Performance Criterion and Financing Assurances Review-Press Release; Staff Report; Supplementary Information; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Guinea's Third Review Under the Extended Credit Facility Arrangement, Request for Modification of Performance Criterion and Financing Assurances Review. Performance against end-December 2018 targets was satisfactory. All performance criteria and the indicative target (IT) on social safety net spending were met. A strong package of adjustment measures was implemented to achieve the end-2018 fiscal target. The ITs on tax revenue and the accumulation of new domestic arrears were not met. Program performance was satisfactory at end-March 2019, with most ITs met. Program-supported reforms advanced. Two of the four structural benchmarks were met, with substantial progress on the other two and full completion expected by. Additional adjustment measures are expected to be implemented to achieve a basic fiscal surplus in 2019, compensating for anticipated higher electricity subsidies and lower tax revenue. In parallel, public investment will be scaled-up to support growth. Advancing programmed tax measures and applying the petroleum prices adjustment mechanism will be key to support revenue mobilization.